Enzymes oxidizing the azo dye 1-phenylazo-2-naphthol (Sudan I) and their contribution to its genotoxicity and carcinogenicity - Stiborova, Marie; Schmeiser, Heinz H; Frei, Eva; Hodek, Petr; Martinek, Vaclav (Current drug metabolism, 2014)
Sudan I [1-(phenylazo)-2-naphthol, C.I. Solvent Yellow 14] is an industrial dye, which was found as a contaminant in numerous foods in several European countries. Because Sudan I has been assigned by the IARC as a Category 3 carcinogen, the European Union decreed that it cannot be utilized as food colorant in any European country. Sudan I induces the malignancies in liver and urinary bladder of rats and mice. This carcinogen has also been found to be a potent mutagen, contact allergen and sensitizer, and exhibits clastogenic properties. The oxidation of Sudan I increases its toxic effects and leads to covalent adducts in DNA. Identification of enzymatic systems that contribute to Sudan I oxidative metabolism to reactive intermediates generating such covalent DNA adducts on the one hand, and to the detoxification of this carcinogen on the other, is necessary to evaluate susceptibility to this toxicant. This review summarizes the identification of such enzymes and the molecular mechanisms of oxidation reactions elucidated to date. Human and animal cytochrome P450 (CYP) and peroxidases are capable of oxidizing Sudan I. Of the CYP enzymes, CYP1A1 is most important both in Sudan I detoxification and its bio-activation. Ring-hydroxylated metabolites and a dimer of this carcinogen were found as detoxification products of Sudan I generated with CYPs and peroxidases, respectively. Oxidative bio-activation of this azo dye catalyzed by CYPs and peroxidases leads to generation of proximate genotoxic metabolites (the CYP-catalyzed formation of the benzenediazonium cation and the peroxidase-mediated generation of one-electron oxidation products), which covalently modify DNA both in vitro and in vivo. The predominant DNA adduct generated with the benzenediazonium cation was characterized to be 8-(phenylazo)guanine. The Sudan I radical species mediated by peroxidases reacts with the -NH2 group in (deoxy)guanosine, generating the 4-[(deoxy)guanosin-N(2)-yl]Sudan I product. Sudan I was also found to be a strong inducer of CYP1A1 and its enzyme activity mediated by the aryl hydrocarbon receptor, thereby increasing its own genotoxic potential and the cancer risk for humans.
Keywords: Animals; Peroxidases; lidé; Coloring Agents; peroxidasy; adukty DNA; Mice; Naphthols; mutageny; Carcinogens; myši; oxidace-redukce; karcinogeny; Oxidation-Reduction; DNA Adducts; barvicí látky; systém (enzymů) cytochromů P-450; krysa rodu Rattus; Enzyme Induction; enzymová indukce; Mutagens; zvířata; naftoly; Rats; Cytochrome P-450 Enzyme System; Humans